The Subordination of the Feminine? Developing a Critical Feminist Approach to the Psychoanalysis of Organizations - Vachhani, Sheena J. (Organization studies, 2012)
This paper investigates the intersections between psychoanalysis and feminist thinking as they may be applied to organization studies by problematizing sexual difference. By critically engaging with the influence of (primarily Lacanian) psychoanalysis, I explore feminist psychoanalytic approaches with their close attention to patriarchy and phallocentrism. More specifically, I engage with the work of Luce Irigaray, whose influential role in French feminist philosophy has occupied what could be termed a difficult or sacrificial position in Lacanian psychoanalysis. I argue that the focus of psychoanalysis on the Phallus as a primary signifier may be fruitfully problematized through a feminist lens (Grosz, 1990), conceived here through Irigaray, and that its usefulness for organizational analysis depends on an ability to recognize, invite and attend to its gendered core. It is argued that Irigaray brings fruitful resources to this debate. Irigaray is concerned with the significant political and ethical dilemmas resulting from the systematic suppression of femininity and this is why her work is significant for a better understanding of gender relations in organizations relating to the exclusion of women, and for new spaces of symbolization and representation. My discussion reveals that, by scrutinizing sexual differences that constitute the subject, one is able to unearth implications for the study of organizations.